2018
DOI: 10.3233/npm-17128
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of early onset neonatal sepsis in neonatal intensive care unit – Mansoura, Egypt

Abstract: Appropriate identification of the source of infection and initiation of an effective management can reduce both mortality and morbidity associated with neonatal sepsis. The challenge is to initiate immediate empirical antibiotic therapy according to a strictly implemented updated antibiotic policy based on an individualized community established antimicrobial sensitivity pattern of microorganisms causing early onset neonatal sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…In the current study, E. coli was the most frequent microorganism isolated from EOS cases (86.2%), which is similar to other studies that found that there is a change in pathogens causing EOS from group B streptococci infections, which have shown a significant decline in recent years due to intrapartum antibiotic prophylaxis to a significant increase in E. coli infections that commonly colonize maternal enteric canal 28. Unlike several studies from Egypt, which found that the most common Gram-negative bacteria causing EOS was Klebsiella , we confirmed our result by detecting the uidA gene encoding the b-glucuronidase enzyme, which is frequently used to identify E. coli 2931…”
Section: Discussionsupporting
confidence: 84%
“…In the current study, E. coli was the most frequent microorganism isolated from EOS cases (86.2%), which is similar to other studies that found that there is a change in pathogens causing EOS from group B streptococci infections, which have shown a significant decline in recent years due to intrapartum antibiotic prophylaxis to a significant increase in E. coli infections that commonly colonize maternal enteric canal 28. Unlike several studies from Egypt, which found that the most common Gram-negative bacteria causing EOS was Klebsiella , we confirmed our result by detecting the uidA gene encoding the b-glucuronidase enzyme, which is frequently used to identify E. coli 2931…”
Section: Discussionsupporting
confidence: 84%
“…Similar results were also obtained in Egypt and Malawi (Mashaly and El-Mahdy 2017;Musicha et al 2017). CoNS were confirmed as a major pathogen isolated in further investigations on smaller groups of patients, mostly neonates in Egypt and Ethiopia (Seliem and Sultan 2018;Sorsa et al 2019). In contrast, a study from Zambia reports that the most frequent pathogen isolated from neonates with sepsis was Klebsiella sp.…”
Section: Epidemiology: Worldwide Distribution Of Staphylococcal Bloodstream Infectionsmentioning
confidence: 87%
“…These results agreed with Seliem and Sultan. 33 and Salama et al 23 who reported that the most causative agent of EONS was Klebsiella pneumoniae. EL-Amir et al 15 demonstrated a prevalence of Gram-negative bacteria among patients with EONS but they found that the most common Gram-negative bacteria causing EONS was E.coli.…”
Section: Discussionmentioning
confidence: 98%